2015
DOI: 10.3389/fenvs.2015.00050
|View full text |Cite
|
Sign up to set email alerts
|

Genome comparison of two Exiguobacterium strains from high altitude andean lakes with different arsenic resistance: identification and 3D modeling of the Acr3 efflux pump

Abstract: Arsenic exists in natural systems in a variety of chemical forms, including inorganic arsenite (As [III]) and arsenate (As [V]). The majority of living organisms have evolved various mechanisms to avoid occurrence of arsenic inside the cell due to its toxicity. Common core genes include a transcriptional repressor ArsR, an arsenate reductase ArsC, and arsenite efflux pumps ArsB and Acr3. To understand arsenic resistance we have performed arsenic tolerance studies, genomic and bioinformatic analysis of two Exig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 72 publications
(92 reference statements)
5
45
0
4
Order By: Relevance
“…Surprisingly, strain SH31 did not show any highly relevant distinctive features. For example, previous studies found four copies of ssb in the genome of strain S17 (Ordoñez et al, 2013, 2015). In Deinococcus radiodurans , the presence of high copy numbers of ssb was proposed to be responsible for its superior radioresistance and DNA repair efficiency (Eggington et al, 2004; Cox and Battista, 2005; Norais et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, strain SH31 did not show any highly relevant distinctive features. For example, previous studies found four copies of ssb in the genome of strain S17 (Ordoñez et al, 2013, 2015). In Deinococcus radiodurans , the presence of high copy numbers of ssb was proposed to be responsible for its superior radioresistance and DNA repair efficiency (Eggington et al, 2004; Cox and Battista, 2005; Norais et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…S17 was likewise obtained, emphasizing the fact that it contains a complete DNA repair system, including UvrABC, MutL-MutS, and bacterial photolyase, and several genes related to toxic compound resistance, such as antibiotics, arsenic, cadmium, and mercury (Ordonez et al, 2013 ). Genomic comparisons with available public genomes from Exiguobacterium suggests that one of the reasons behind high resistance to arsenic in S17 is the presence of the acr3 gene, a known contributor to cell detoxification against arsenite, one of the most toxic arsenic species (Ordoñez et al, 2015 ). All Exiguobacterium strains have a conserved arsB gene playing a role similar to acr3 , but S17 is the only one bearing both genes.…”
Section: Microbial Diversitymentioning
confidence: 99%
“…Ver3 (Albarracín et al, 2014 ), and an arsenical resistance efflux pump from Exiguobacterium sp. S17 (Ordoñez et al, 2015 ) for which medical and bioremediation applications, respectively, are envisaged. But still, much effort is required to unravel novel functions for this and other molecules that dwell in a unique biological treasure despite its being hidden high up, in the remote Andes.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…S17. This halotolerant, UV-resistant microorganism [ 48 ] was originally isolated from modern stromatolite at L. Socompa (3,570 m; Fig 1 ) [ 41 ] being able to grow at concentrations up to 100 mM As[V] and 5mM As[III] [ 45 , 50 ]. Neighbor-Joining and maximum likelihood trees based on 16SrRNA gene sequences and MLSA of Exiguobacterium sp.…”
Section: Discussionmentioning
confidence: 99%
“…S10B and S34, yielded genes putatively encoding essential traits for survival under multiple environmental extreme conditions, e.g., high levels of UV radiation, elevated salinity, and the presence of poisoning arsenic concentrations [ 18 , 45 , 48 50 ]. Likewise, genes putatively coding for the bacteriorhodopsin protein family were found showing sequential features indicating the presence of proteorhodopsins and xantorhodopsins [ 18 , 45 47 ]. The former findings called for a more detailed, molecular investigation of the mechanisms involved in the resistance of these strains to extreme but common impairing factors in its original environment.…”
Section: Introductionmentioning
confidence: 99%